Factores psicosociales y estrés laboral de la enfermera en el servicio de emergencia del Hospital de Alta Complejidad. - Rumay Chanduco, Doris (2020)
The present cross-sectional descriptive type research was conducted with the purpose of determining the relationship between psychosocial factors and degree of occupational stress in the nurses of the emergency service of the High Complexity Hospital "Virgen de la Puerta", the population The sample was of 32 nurses to whom two instruments were applied: psychosocial factors and scale of nursing work stress (NSS). The information obtained was processed and analyzed using the Chi-square statistical tests, concluding: Psychosocial factors in nurses in the emergency service in the Participation Involvement and Responsibility dimension, 71.9% were inadequate and only 28.1% were adequate, in Training Information and Communication 50% adequate as inadequate, in Time Management 81.2% inadequate and 18.8% adequate, in Group Cohesion 56.3% adequate and 43.7% inadequate and in harassment or mobbing reported as not 96.9%. 65.6% of nurses report a moderate degree of work stress, 34.4% low, no high work stress is reported. The psychosocial factors of training, information and communication, in Time management and group cohesion, a highly significant statistical relationship was obtained p = 0.009, p = 0.005, p = 0.000 respectively; in participation, involvement and responsibility was significant p = 0.034.